2017
DOI: 10.1007/s12237-017-0313-3
|View full text |Cite
|
Sign up to set email alerts
|

Floodgate Operations and Fish Communities in Tidal Creeks of the Lower Fraser River (British Columbia, Canada)

Abstract: Tidal creeks in large coastal deltas can be important habitat for fish but are often highly modified by human activities. Connectivity between tributary creeks and mainstem channels is often constrained by structures such as dikes and floodgates, designed to protect urban and agricultural areas from flooding. While they play important roles in flood mitigation, floodgates can diminish habitat quality and block fish from accessing tidal creeks. It is likely that floodgates differ in their operations and may con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Further, the tidal characteristics and low‐lying nature of the Fraser Valley have precipitated the construction of floodgates along many of the tributaries (Thomson and Confluence Environmental Consulting 1999). The operation of floodgates in the Lower Fraser has been shown to create hotspots for invasive species, reduce native fish diversity, and cause hypoxic conditions up to 100 m upstream (Gordon et al 2015, Scott et al 2016, Seifert and Moore 2018). While improved management of the operation of these floodgates may mitigate some of these negative impacts (Seifert and Moore 2018), even when completely open, floodgates alter flow velocities and can become perched or otherwise inaccessible (Haro et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the tidal characteristics and low‐lying nature of the Fraser Valley have precipitated the construction of floodgates along many of the tributaries (Thomson and Confluence Environmental Consulting 1999). The operation of floodgates in the Lower Fraser has been shown to create hotspots for invasive species, reduce native fish diversity, and cause hypoxic conditions up to 100 m upstream (Gordon et al 2015, Scott et al 2016, Seifert and Moore 2018). While improved management of the operation of these floodgates may mitigate some of these negative impacts (Seifert and Moore 2018), even when completely open, floodgates alter flow velocities and can become perched or otherwise inaccessible (Haro et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The operation of floodgates in the Lower Fraser has been shown to create hotspots for invasive species, reduce native fish diversity, and cause hypoxic conditions up to 100 m upstream (Gordon et al 2015, Scott et al 2016, Seifert and Moore 2018). While improved management of the operation of these floodgates may mitigate some of these negative impacts (Seifert and Moore 2018), even when completely open, floodgates alter flow velocities and can become perched or otherwise inaccessible (Haro et al 2004). In addition to floodgates, the ever‐expanding road network has created additional barriers, with over 170,000 closed bottom culverts impeding fish passage across British Columbia (Fish Passage Technical Working Group 2014).…”
Section: Introductionmentioning
confidence: 99%
“…; Krueger et al. ; Seifert and Moore ), and in some cases these efforts have been quite successful. For example, restoration efforts focused on floodplain connection in the upper Chilliwack River watershed of British Columbia identified that between 27% and 34% of the overall Coho Salmon Oncorhynchus kisutch smolt migration could be attributed to those restored habitat types (Ogston et al.…”
mentioning
confidence: 99%
“…Using the combination of structural and nonstructural measures can be a valuable solution to prevent, reduce, prepare for, respond to, and recover from flooding hazards. Among such measures is the optimal design of stormwater drainage network capacity and its structures (Farzin & Valikhan Anaraki 2020), optimal operation of floodwater transfer and control structures (Seifert & Moore 2018), design of a real-time automated system for the stormwater drainage pumping station, multi-objective optimization of reservoir management, and operation (Meng et al 2019), and optimization models to determine sustainable development policies and structural measures planning (Nones 2015).…”
mentioning
confidence: 99%